Implementasi Good Forest Governance dalam Pengelolaan Hutan Lindung di Kabupaten Bantaeng - Taufik, Ahmad; Hamrun, Hamrun; Harakan, Ahmad (Jurnal Analisis Sosial Politik, 2017)
This article explores the implementation of good forest governance in the management of protection forest in Bantaeng and processes as well as the management stages of protected forest areas in order to utilize and continuity stay awake. This study used a qualitative approach to explainingd main problems discussed by descriptive method. The results of this study found that implementation of forest management in Bantaeng get support from the local government as a form of implementation of good forest governance in the management of protection forest areas include the Strengthening national policy, and as well as the establishment and strengthening of community institutions. While the processes and management stages that lead to cooperation between forum rembuk hutan desa with LSM Balang held village discussions about village forest management for welfare enhancement in Labbo, Pattaneteang and Campaga. Artikel ini mengeksplorasi implementasi good forest governance dalam pengelolaan hutan lindung di Kabupaten Bantaeng dan proses serta tahapan pengelolaan kawasan hutan lindung agar pemanfaatan dan kelestariannya tetap terjaga. Penelitian ini menggunakan pendekatan kualitatif untuk menjelaskan secara metode deskriptif permasalahan pokok yang dibahas. Hasil penelitian ini menemukan bahwa pelaksanaan pengelolaan hutan di Kabupaten Bantaeng memperoleh dukungan dari pemerintah daerah sebagai wujud pelaksanaan good forest governance dalam pengelolaan hutan lindung dukungan tersebut meliputi Penguatan kebijakan pemerintah pusat, dan pembentukan serta penguatan lembaga kemasyarakatan. Sedangkan proses dan tahapan pengelolaan yang mengarah pada kerjasama forum rembuk hutan desa dengan LSM Balang menggelar diskusi kampung peningkatan kesejahteraan masyarakat desa pengelolaan hutan desa di Labbo, Pattaneteang dan Campaga.